Formulating treatment recommendation as a logical consequence of the diagnosis in post-surgical oncological visits. Issue 6 (June 2016) - Fatigante, Marilena; Alby, Francesca; Zucchermaglio, Cristina; Baruzzo, Mattia
Highlights: In post-surgical oncological visits, the study examines an oncologist's practices to deliver diagnosis and treatment recommendation. The itinerary from diagnostic assessment to treatment proposal includes 4 activities overall. The oncologist delivers diagnosis and presents treatment options orienting to the patient's expectations. The treatment recommendation is formulated as a logical consequence deriving from the available diagnostic information. Presenting the treatment as a logical consequence can supersede Shared Decision Making with the patients. Abstract: Objective: the article analyzes how a doctor delivers diagnoses and recommends treatment in a set of post-surgical oncological visits. The pattern of activities are explored in two different cases: when all diagnostic information is available, and when information is still missing. Methods: The data consist of 12 video-recorded visits of breast cancer patients to a senior oncologist. Conversation analysis is employed to analyze sequences in which the delivery of diagnosis and treatment recommendation unfold. Results: The oncologist formulates the treatment recommendation as a logical consequence deriving from the available diagnostic information. In cases when definitive diagnostic information on the cancer type is missing, the oncologist opts to anticipate hypothetical diagnostic scenarios, and to draw the therapeutic alternatives as logical outcomes envisionable from each of the different scenarios. Conclusion: The communicative practice appears functional to encourage the patients' acceptance of a single treatment option rather than present the patients to and involve them in deliberating over multiple available treatment alternatives. Practice implications: Rather than a normative adoption of existing protocols of communication in cancer care, a better understanding of communication practices in use can help practitioners to reflect upon and make intentional choices about different arrangements for the patient's participation.